2007
DOI: 10.1152/jn.00587.2007
|View full text |Cite
|
Sign up to set email alerts
|

Visual Deprivation Alters the Development of Cortical Multisensory Integration

Abstract: It has recently been demonstrated that the maturation of normal multisensory circuits in the cortex of the cat takes place over an extended period of postnatal life. Such a finding suggests that the sensory experiences received during this time may play an important role in this developmental process. To test the necessity of sensory experience for normal cortical multisensory development, cats were raised in the absence of visual experience from birth until adulthood, effectively precluding all visual and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 60 publications
7
82
1
Order By: Relevance
“…1, revealed physiologically active neurons (n = 415), the majority of which (67.7% ± 7.6 SD) were responsive to visual stimulation. By contrast, similar recordings from the FAES in adult hearing cats (n = 3) in this and in previous studies (2,22,23,(25)(26)(27)(28) showed a strong preference auditory responsivity, although a small proportion of nonauditory responses also occurred (Fig. 1).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…1, revealed physiologically active neurons (n = 415), the majority of which (67.7% ± 7.6 SD) were responsive to visual stimulation. By contrast, similar recordings from the FAES in adult hearing cats (n = 3) in this and in previous studies (2,22,23,(25)(26)(27)(28) showed a strong preference auditory responsivity, although a small proportion of nonauditory responses also occurred (Fig. 1).…”
Section: Resultssupporting
confidence: 80%
“…What is known of the FAES suggests that unmasking may have at least a partial role in its reorganization following deafness. In hearing animals, ∼30% of FAES neurons show modulation of auditory responses by activation of an adjacent somatosensory area (24), and ∼30% of neurons can be influenced by visual stimulation (23,27). Therefore, with a reduction of auditory inputs after deafness, it would be expected that existing nonauditory inputs to the FAES would be unmasked.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cross-sensory modulations may target subsets of neurons based on their response level, laminar location, and neuron type within each rearing condition. The fact that the auditory clicks failed to drive any barrel cortex neurons under any conditions in the present study indicates that the cross-sensory multisensory interactions observed here are modulatory in nature (Dehner et al, 2004;Lakatos et al, 2007;Carriere et al, 2008), as opposed to the directly driven responses found in association cortex (Wallace et al, 1992;Carriere et al, 2007), and may account for the difficulty in detecting multisensory influences in primary sensory cortex. Surprisingly, the modulatory influence is present even in normally reared rats and is maximally enhanced when whisker deprivation is coupled with click rearing.…”
Section: Discussioncontrasting
confidence: 46%
“…The same seems to be true for subcortical multisensory regions such as in the superior colliculus [69]. Similar results have been obtained in human infants that show age-dependent effects on reaction times when tested in localization of auditory, visual or audiovisual stimuli [70]. Nevertheless, some basic multisensory processes seem to be in place quite early in human life as indicated by data from 5-month-old infants regarding the discrimination of visual, auditory or audiovisual rhythms [71] and processing of audiovisual correspondences between the height of a pitch and the height of a visual stimulus [56].…”
Section: Maturation E Ectssupporting
confidence: 82%